Panic Disorder and Agoraphobia in OCD patients: Clinical profile and possible treatment implications - Torres, Albina Rodrigues [UNESP]; Ferrao, Ygor. A.; Shavitt, Roseli G.; Diniz, Juliana B.; Costa, Daniel L. C.; Rosario, Maria Conceicao do; Miguel, Euripedes C.; Fontenelle, Leonardo F. (Elsevier B.V., 2014)
Objective: Panic Disorder (PD) and agoraphobia (AG) are frequently comorbid with obsessive compulsive disorder (OCD), but the correlates of these comorbidities in OCD are fairly unknown. The study aims were to: 1) estimate the prevalence of PD with or without AG (PD), AG without panic (AG) and PD and/or AG (PD/AG) in a large clinical sample of OCD patients and 2) compare the characteristics of individuals with and without these comorbid conditions.Method: A cross-sectional study with 1001 patients of the Brazilian Research Consortium on Obsessive Compulsive Spectrum Disorders using several assessment instruments, including the Dimensional Yale Brown Obsessive Compulsive Scale and the Structured Clinical Interview for DSM-IV-TR Axis I Disorders. Bivariate analyses were followed by logistic regression models.Results: The lifetime prevalence of PD was 15.3% (N = 153), of AG 4.9% (N = 49), and of PD/AG 20.2% (N = 202). After logistic regression, hypochondriasis and specific phobia were common correlates of the three study groups. PD comorbidity was also associated with higher levels of anxiety, having children, major depression, bipolar I, generalized anxiety and posttraumatic stress disorders. Other independent correlates of AG were: dysthymia, bipolar 11 disorder, social phobia, impulsive compulsive internet use, bulimia nervosa and binge eating disorder. Patients with PD/AG were also more likely to be married and to present high anxiety, separation anxiety disorder, major depression, impulsive compulsive internet use, generalized anxiety, posttraumatic stress and binge eating disorders.Conclusions: Some distinct correlates were obtained for PD and AG in OCD patients, indicating the need for more specific and tailored treatment strategies for individuals with each of these clinical profiles. (C) 2014 Elsevier Inc. All rights reserved.